Evaluation of the Use of PEEK Material in Implant-Supported Fixed Restorations by Finite Element Analysis - Tekin, S.; Deger, Y.; Demirci, F. (Wolters Kluwer Medknow Publications, 2019)
Aims: The purpose of this study is to compare the stresses occurring in the peri-implant bones, implants, crowns, abutments, and screws after loading through finite element analysis by using the poly-ether-ether-ketone (PEEK) materials, which are alternative to titanium abutment and metal supported restorations and to try to reduce the level of neck resorption. Materials and Methods: In our study, three-dimensional modeling of 2 PEEK and titanium abutments, metal-ceramic, and monolithic PEEK upper central dental restorations were made on four titanium implants (Biohorizons (R) Implant Systems Ins., Birmingham, AL, USA) with diameters of 3.8 mm and 10.5 mm and four groups were obtained. Then, a stress analysis of the finite element was performed by applying a 178 N oblique force of 45 degrees to the long axis of the tooth 2 mm below the incisal edge of the model's palatal surface. Results: It has been observed that the PEEK material reduces the stresses caused by the force applied on itself during all tests. In all groups, PEEK abutments and PEEK crowns have reduced stress on the abutment. The most significant difference is observed in the stresses on the crowns and screws. When the stresses on the crown are examined, the use of PEEK crown reduces the stresses on itself and the use of PEEK abutment increases the stresses on the crown. Conclusions: The stress on the implant system can be changed through the usage of different prosthetic materials.
Keywords: Dental implant; finite element analysis; poly-ether-ether-ketone